MENINGKATKAN KECERDASAN INTERPERSONAL ANAK KELOMPOK B MELALUI KEGIATAN COOKING CLASS BERBASIS MAKANAN BUDAYA JAMBI DI TK ISLAM AL AZHAR 57 JAMBI - Amanah Sholeha; Hendra Sofyan; Uswatul Hasni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of interpersonal intelligence among 5–6-year-old children at AL AZHAR 57 Islamic Kindergarten in Jambi. Based on the results of observations, there are still children who are unable to take responsibility, do not socialize well with their peers, and are hesitant to express their opinions and cooperate in group activities. This study aims to improve the interpersonal intelligence of children in Group B through a cooking class based on Jambi’s cultural cuisine at AL AZHAR 57 Islamic Kindergarten in Jambi. This study is a Classroom Action Research (CAR) using the Kemmis and Taggart model, which consists of the planning, implementation, observation, and reflection stages. The research was conducted at AL AZHAR 57 Islamic Kindergarten in Jambi. The population in this study consisted of 35 children, with a sample of 22 children from Group B. The instrument used was an observation sheet to monitor the development of the children’s interpersonal intelligence during the cooking class based on Jambi’s cultural cuisine. The results of the study indicate that the children’s interpersonal intelligence prior to the intervention was in the “beginning to develop” category, at a rate of 30.59%. After implementing the Jambi cultural food-based cooking class activities over three cycles, the children’s interpersonal intelligence improved at each session, reaching 83.13% in the “very well developed” category. Thus, the Jambi cultural food-based cooking class activities were proven to improve the interpersonal intelligence of Group B children at AL AZHAR 57 Islamic Kindergarten in Jambi.